Transcriptomic and Metabolomic Analyses Reveal Key Metabolites, Pathways and Candidate Genes in Sophora davidii (Franch.) Skeels Seedlings Under Drought Stress - Zhao, Xin; Huang, Li-Juan; Sun, Xiao-Fu; Zhao, Li-Li; Wang, Pu-Chang (Frontiers in Plant Science, 2022)
Soil aridification and desertification are particularly prominent in China's karst areas, severely limiting crop yields and vegetation restoration. Therefore, it is very important to identify naturally drought-tolerant plant species. Sophora davidii (Franch.) Skeels is resistant to drought and soil infertility, is deeply rooted and is an excellent plant material for soil and water conservation. We studied the transcriptomic and metabolomic changes in S. davidii in response to drought stress (CK, control; LD, mild drought stress; MD, moderate drought stress; SD, severe drought stress). S. davidii grew normally under LD and MD stress but was inhibited under SD stress; the malondialdehyde (MDA), hydrogen peroxide (H2O2), soluble sugar, proline, chlorophyll a, chlorophyll b and carotenoid contents and ascorbate peroxidase (APX) activity significantly increased, while the superoxide dismutase (SOD), peroxidase (POD) and catalase (CAT) activities and soluble protein content significantly decreased. In the LD/CK, MD/CK and SD/CK comparison groups, there were 318, 734 and 1779 DEGs, respectively, and 100, 168 and 281 differentially accumulated metabolites, respectively. Combined analysis of the transcriptomic and metabolomic data revealed the metabolic regulation of S. davidii in response to drought stress. First, key candidate genes such as PRR7, PRR5, GI, ELF3, PsbQ, PsaK, INV, AMY, E2.4.1.13, E3.2.1.2, NCED, PP2C, PYL, ABF, WRKY33, P5CS, PRODH, AOC3, HPD, GPX, GST, CAT and SOD1 may govern the drought resistance of S. davidii. Second, three metabolites (oxidized glutathione, abscisic acid and phenylalanine) were found to be related to drought tolerance. Third, several key candidate genes and metabolites involved in 10 metabolic pathways were identified, indicating that these metabolic pathways play an important role in the response to drought in S. davidii and possibly other plant species.